Animal Death - Johnston, Jay; Probyn-Rapsey, Fiona (Animal Publics, 2013)
Animal death is a complex, uncomfortable, depressing, motivating and sensitive topic. For those scholars participating in Human-Animal Studies, it is - accompanied by the concept of 'life' - the ground upon which their studies commence, whether those studies are historical, archaeological, social, philosophical, or cultural. It is a tough subject to face, but as this volume demonstrates, one at the heart of human-animal relations and human-animal studies scholarship.